Ruthenium Oxide Hexacyanoferrate as an Effective Electrode Modifier for Amperometric Detection of Iodate and Hydrogen Peroxide - Totka Dodevska; Ivan Shterev; Yanna Lazarova; Dobrin Hadzhiev (Acta Chimica Slovenica, 2020)
Ruthenium oxide hexacyanoferrate (RuOHCF) film was electrochemically deposited onto a glassy carbon (GC) surface using consecutive cyclic voltammetry as a facile and green synthetic strategy. The electrochemical behaviour and electrocatalytic properties of the modified electrode RuОHCF/GC were evaluated with regards to electroreduction of hydrogen peroxide and iodate in a strong acidic medium (pHs 1.0 – 2.0) by using different electrochemical techniques, including cyclic voltammetry and amperometry at a constant potential. Electrochemical studies indicated that RuОHCF/GC possess a high catalytic activity in both studied reactions, fast response and good reproducibility of the current signal. The RuОHCF/GC exhibits enhanced electrocatalytic behaviour compared with other modified electrodes reported before. The simple and reproducible procedure for electrode fabrication, the wide linear range, anti-interference performance and long-time stability of the RuОHCF/GC make it a promising sensing material for practical quantitative determination of hydrogen peroxide and iodate. Remarkably, the reported modified electrode provided superior sensitive (1050 µA mM–1 cm–2) and highly selective amperometric detection of iodate.